A core-shell magnetic molecular imprinted polymer material and its preparation method and application

By using core-shell magnetic molecular imprinting polymer materials, the high-efficiency adsorption and separation of various steroid hormones in the blood are solved, and an efficient, fast and reusable adsorption effect is achieved.

CN117531486BActive Publication Date: 2025-03-18BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202311490498.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2025-03-18
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively adsorb and separate a variety of steroid hormones with large structural differences in blood, and traditional adsorbents have problems such as low selectivity, poor reuseability, and difficulty in separation.

Method used

A core-shell magnetic molecular imprinted polymer material is used, which is made of silica-modified iron tetraoxide nanoparticles as the core, and a blotting polymer layer of betamethasone, 3,3-dihydroxybenzidine and parabenzoquinone are used as the shell to form rough particles of 400-900 nm, which has good adsorption selectivity and reusability.

Benefits of technology

It has achieved efficient adsorption and separation of 25 steroid hormones with large structural differences in the blood, with an adsorption rate of more than 90%, a recovery rate of more than 70%, and the material has good regeneration ability, and the reuse is still maintained at a high recovery rate of five times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117531486B_ABST
    Figure CN117531486B_ABST
Patent Text Reader

Abstract

The present invention relates to a core-shell magnetic molecular imprinted polymer material, a preparation method and its application in enriching 25 steroid hormones in blood. The present invention is based on the polymerization reaction of 3,3-dihydroxybenzidine and p-benzoquinone, precipitates and polymerizes on the surface of magnetic ferroferric oxide nanoparticles modified with silicon dioxide to form a polymer layer, and simultaneously uses virtual template betamethasone for imprinting treatment to obtain a core-shell magnetic molecular imprinted polymer material. The core-shell magnetic molecular imprinted polymer material prepared by the present invention has good magnetic responsiveness. The adsorption test of 25 steroid hormones shows that the core-shell magnetic molecular imprinted polymer material of the present invention has good adsorption and desorption effects, and is convenient to separate and recyclable after adsorption, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a core-shell magnetic molecular imprinted polymer and a preparation method thereof and application of the core-shell magnetic molecular imprinted polymer as a material for adsorbing 25 types of steroid hormones, belonging to the technical field of molecular imprinted polymers. Background Art

[0002] Steroid hormones, also known as steroid hormones, are a class of tetracyclic aliphatic hydrocarbon compounds with extremely important medical value. They play a clear role in maintaining life, regulating sexual function, body development, immune regulation, skin disease treatment and birth control. At the same time, as a special type of endocrine disrupting chemical, steroid hormones are closely related to a series of human endocrine disorders. Toxicological studies have also reported that steroid hormones may be harmful to organisms even at trace levels. Since the concentration of these compounds in blood samples is usually at trace levels, the pretreatment of steroid hormones is crucial for further analysis.

[0003] At present, the commonly used method for pretreatment of steroid hormones is solid phase extraction. Traditional SPE has disadvantages such as many extraction steps, long operation time, large amount of organic solvents and the inability to reuse the extraction column. Therefore, new SPE technologies that are efficient, fast and reusable have received attention and development. Regardless of the SPE technology, efficient and highly selective adsorption materials are the prerequisites for determining the sample pretreatment effect. However, traditional adsorbents have disadvantages such as low selectivity, poor reusability and difficulty in separation.

[0004] Molecularly imprinted polymers are often used in combination with solid phase extraction for the separation of small molecules due to their good mechanical and chemical stability, high selectivity and long life, and can be used as one of the candidate materials for the separation of steroid hormones. However, due to the wide variety of steroid hormones in the blood and their different structures, the existing literature on the enrichment and separation of steroid hormones is mostly targeted at one or a class of steroid hormones with similar structures, and there is no literature on steroid hormones with large structural differences. Summary of the invention

[0005] The object of the present invention is to provide a core-shell magnetic molecular imprinted polymer material and a preparation method thereof, wherein the core-shell magnetic molecular imprinted polymer material can have good adsorption capacity and adsorption selectivity for 25 steroid hormones with greatly different structures in blood. The 25 steroid hormones are: progesterone, 11-deoxycorticosterone, corticosterone, 18-hydroxycorticosterone, aldosterone, 17-hydroxypregnenolone, 17-hydroxyprogesterone, 11-deoxycortisol, 21-deoxycortisol, cortisol, cortisone, dehydroepiandrosterone, androstenedione, estrone, testosterone, estradiol, estriol, dihydroxytestosterone, 11-hydroxyandrostenedione, 11-ketoandrostenedione, 11-hydroxytestosterone, 11-ketotestosterone, epitestosterone, androsterone, and epiandrosterone.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned object of the invention is described in detail below.

[0007] The core of the core-shell magnetic molecular imprinted polymer material of the present invention is a silicon dioxide-modified ferroferric oxide nanoparticle, and the shell is an imprinted polymer layer of 3,3-dihydroxybenzidine and p-benzoquinone with betamethasone as a virtual template, which is a rough particle of 400-900nm.

[0008] The method for preparing a core-shell magnetic molecular imprinted polymer material according to the invention comprises the following steps:

[0009] 1) 0.41-1.22 g of anhydrous ferric chloride and 1.8-5.4 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted in a 200° C. oven for 8 h. After the reaction was completed, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60° C. vacuum drying oven for 6 h.

[0010] 2) Take 400-800 mg of the magnetic ferroferric oxide obtained above and 20 mL of 1 mol / L hydrochloric acid, mix and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water under mechanical stirring, then dilute 400-1200 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, placed in a vacuum drying oven at 60 ° C and dried for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0011] 3) The obtained silica-modified ferroferric oxide nanoparticles were dispersed in 40 mL of ethanol, and then betamethasone and 3,3-dihydroxybenzidine were added thereto and dispersed uniformly by ultrasonication. Then, p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under mechanical stirring, and condensed and refluxed at 70°C for 2 h under mechanical stirring of 500 r / min, wherein the molar ratio of betamethasone to 3,3-dihydroxybenzidine was 1:2 to 1:10, and the molar ratio of betamethasone to p-benzoquinone was 1:10 to 1:50. After the reaction was completed, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with an eluent of methanol / acetic acid (volume ratio of 9:1), and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60°C for 6 h to obtain a core-shell magnetic molecular imprinted polymer material.

[0012] The core-shell magnetic molecular imprinted polymer material of the invention utilizes the hydrogen bonding of polymer amino and hydroxyl groups, the π-π interaction of benzene rings, and the imprinted cavity formed by betamethasone to enrich and adsorb 25 steroid hormones with large structural differences in blood samples.

[0013] The effectiveness verification and application of a core-shell magnetic molecular imprinted polymer material described in the invention include the following steps:

[0014] 1) Take 0.05-0.2 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of a prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex at room temperature for 25 minutes, and after complete elution, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 70% except for progesterone and androsterone, which are more than 50%. The recovery rate is still high after repeated use for five times.

[0015] 2) Application in enriching 25 steroid hormones in blood samples:

[0016] 100 μL of plasma was vortexed for 1 min and then allowed to stand in the dark for 5 min. 150 μL of methanol was added and vortexed for 1 min. 200 μL of water was added and vortexed for 1 min. The mixture was centrifuged (4°C, 12000 rpm, 15 min). 300 μL of the supernatant was taken and 0.1-0.6 mg of the prepared material was added thereto. The mixture was vortexed for 30 min. The supernatant was removed and the material was washed with deionized water. 300 μL of methanol was added and vortexed for 25 min to elute the hormone. After magnetic separation, 200 μL of the supernatant was taken and blown to dryness with nitrogen. The mixture was then redissolved with 100 μL of 30% methanol and injected for measurement.

[0017] Beneficial effects of the present invention:

[0018] (1) The polymer layer has benzene rings, amino groups and hydroxyl groups, which can efficiently bind to steroid hormones through hydrogen bonding and the π-π interaction of the benzene rings. The thickness of the imprinted polymer layer can be controlled by adjusting the amount of functional monomers added and the reaction time. The imprinted polymer particles have the ability to selectively adsorb compounds with similar molecular structures to the virtual template, which can effectively identify steroid hormones in the blood and further improve the adsorption effect of 25 steroid hormones in blood samples.

[0019] (2) Core-shell magnetic molecular imprinted polymer particles are easier to separate and recycle, and have high application stability. Surface imprinting can effectively reduce the occurrence of reduced adsorption efficiency due to indentation of binding sites, and has good application prospects.

[0020] Characterization and validation of beneficial effects

[0021] (1) The core-shell magnetic molecularly imprinted polymer prepared by the method of the present invention was placed in a mortar, a small amount of potassium bromide was added, and the mixture was evenly ground. The mixture was poured into a mold, and the sample was pressed into a thin sheet using a tablet press. The sample was characterized using a Fourier transform infrared spectrometer.

[0022] (2) The core-shell magnetic molecular imprinted polymer prepared by the method of the present invention was dispersed in an ethanol solution and then dropped onto a silicon wafer. It was then fixed on a sample stage with a conductive glue and then sprayed with gold. The morphology was observed with a scanning electron microscope (SEM).

[0023] (3) The core-shell type magnetic molecular imprinted polymer prepared by the method of the present invention is dispersed with an ethanol solution and then dropped onto a silicon wafer. It is then fixed on a sample stage with a conductive glue and then sprayed with gold. The elemental composition of the core-shell type magnetic molecular imprinted polymer is scanned by energy dispersive spectroscopy (EDS).

[0024] (4) Take 0.1 mg of the core-shell magnetic molecular imprinting polymer prepared by the method of the present invention and add it to 100 μL of a prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 min to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex at room temperature for 25 min, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones.

[0025] (5) The adsorption rate of the material for 25 steroid hormones was more than 90%, and the recovery rate was more than 50%. The reusability was very good. After five adsorption-desorption cycles, the adsorption rate of the 25 steroid hormones did not change much, indicating that the adsorption-desorption performance of the core-shell type magnetic molecular imprinted polymer material obtained by the method of the present invention was good, and the imprinted holes did not change significantly, indicating that the core-shell type magnetic molecular imprinted polymer material had excellent regeneration ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the FTIR graph of the core-shell magnetic molecular imprinted polymer obtained in Example 7 of the present invention;

[0027] Figure 2 is a SEM image of the core-shell magnetic molecular imprinted polymer obtained in Example 7 of the present invention;

[0028] Figure 3 is the EDS image of the core-shell magnetic molecular imprinted polymer obtained in Example 7 of the present invention;

[0029] Figure 4 Schematic diagram of the adsorption rate and recovery rate of 25 steroid hormones by the core-shell magnetic molecular imprinted polymer obtained in Example 7 of the present invention;

[0030] Figure 5 This is a graph showing the cyclic performance of the core-shell magnetic molecularly imprinted polymer obtained in Example 7 of the present invention for separating 25 steroid hormones; DETAILED DESCRIPTION

[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0032] Example 1

[0033] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0034] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0035] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0036] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 64.9 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 486.4 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecule, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0037] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0038] Example 2

[0039] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0040] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0041] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0042] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 129.7 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 486.4 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0043] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0044] Example 3

[0045] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0046] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0047] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0048] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 196.4 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 486.4 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecule, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0049] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0050] Example 4

[0051] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0052] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0053] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0054] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 259.5 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 486.4 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecule, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0055] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0056] Example 5

[0057] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0058] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0059] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0060] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 324.4 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 486.4 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecule, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0061] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0062] Example 6

[0063] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0064] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0065] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0066] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 162.1 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0067] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0068] Example 7

[0069] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0070] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0071] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0072] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0073] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0074] Example 8

[0075] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0076] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0077] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0078] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, dissolve 486.4 mg of p-benzoquinone in 60 mL of ethanol, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condense and reflux at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate is separated by magnetic attraction, and the obtained black product is washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecule, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0079] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0080] Example 9

[0081] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0082] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0083] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0084] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 648.6 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecule, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0085] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0086] Example 10

[0087] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0088] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0089] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0090] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 810.7 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0091] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0092] Embodiment 11

[0093] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0094] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0095] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 400 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0096] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0097] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0098] Example 12

[0099] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0100] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0101] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water under mechanical stirring, then dilute 1200 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0102] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0103] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0104] Example 13

[0105] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0106] 1) 0.41 g of anhydrous ferric chloride and 1.8 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and placed in a 60 ° C vacuum drying oven for 6 h.

[0107] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0108] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0109] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0110] Embodiment 14

[0111] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0112] 1) 1.22 g of anhydrous ferric chloride and 5.4 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0113] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0114] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0115] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0116] Embodiment 15

[0117] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0118] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0119] 2) Take 600 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0120] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0121] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0122] Example 16

[0123] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0124] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0125] 2) Take 800 mg of the magnetic ferroferric oxide obtained above and 1 mol / L hydrochloric acid and mix them for ultrasonic treatment for 10 minutes to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash them three times with deionized water to remove excess hydrochloric acid, and then disperse them in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonic treatment for 20 minutes to fully disperse them, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and continue mechanical stirring at room temperature for 5 hours. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, placed in a vacuum drying oven at 60°C and dried for 6 hours to obtain silica-modified ferroferric oxide nanoparticles.

[0126] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0127] 4) Take 0.1 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes, and after elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0128] Embodiment 17

[0129] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0130] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0131] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0132] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0133] 4) Take 0.05 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes. After elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 50% for progesterone and androsterone, and the others are all more than 70%. The recovery rate is still high after repeated use for five times.

[0134] Embodiment 18

[0135] A method for preparing a core-shell magnetic molecular imprinted polymer and material effectiveness verification comprises the following steps:

[0136] 1) 0.81 g of anhydrous ferric chloride and 3.6 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 200 ° C in an oven for 8 h. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and dried in a 60 ° C vacuum drying oven for 6 h.

[0137] 2) Take 400 mg of the magnetic ferroferric oxide obtained above and mix with 1 mol / L hydrochloric acid and ultrasonically treat for 10 min to activate the surface hydroxyl groups of ferroferric oxide nanoparticles, wash with deionized water three times to remove excess hydrochloric acid, and then disperse it in a mixed solvent system of 200 mL ethanol / water (volume ratio of 4:1), ultrasonically treat for 20 min to fully disperse, add 5 mL of ammonia water to it under mechanical stirring, then dilute 800 μL of TEOS with ethanol to 20 mL, and then drip it into the reaction system at a speed of 1 d / s under the condition of 500 r / min mechanical stirring, and continue mechanical stirring at room temperature for 5 h. After the reaction is completed, the precipitate is separated by magnetic attraction, and the obtained black product is washed alternately with ethanol and deionized water three times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain silica-modified ferroferric oxide nanoparticles.

[0138] 3) Weigh 100 mg of silica-modified ferroferric oxide nanoparticles and disperse them in 40 mL of ethanol, then add 40 mg of betamethasone and 194.6 mg of 3,3-dihydroxybenzidine, and disperse them evenly by ultrasonication. Then, 324.3 mg of p-benzoquinone was dissolved in 60 mL of ethanol, and then dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and condensed and refluxed at 70 ° C for 2 h under the condition of mechanical stirring. After the reaction, the precipitate was separated by magnetic attraction, and the obtained black product was washed three times with the eluent methanol / acetic acid (volume ratio of 9:1) to elute the template molecules, and then washed three times with deionized water and ethanol alternately, and then placed in an oven at 60 ° C for 6 h to obtain a core-shell magnetic molecular imprinting polymer material.

[0139] 4) Take 0.2 mg of the core-shell magnetic molecular imprinted polymer prepared by the method of the present invention and add it to 100 μL of the prepared mixed standard solution of 25 steroid hormones. After vortexing at room temperature for 30 minutes to reach adsorption equilibrium, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the remaining 25 steroid hormones in the solution, and calculate the adsorption rate of the material for the 25 steroid hormones. After pouring out the excess solution, add 100 μL of methanol to the remaining material, vortex and oscillate at room temperature for 25 minutes. After elution is complete, separate the precipitate by magnetic attraction, dilute the supernatant and use LC-MS to determine the concentration of the 25 steroid hormones eluted in the solution, and calculate the adsorption rate and recovery rate of the 25 steroid hormones. The adsorption rate is ≥90%, and the recovery rate is more than 70% except for progesterone and androsterone, which is more than 50%. The recovery rate is still high after repeated use for five times.

[0140] Embodiment 19

[0141] A core-shell magnetic molecular imprinted polymer for practical blood sample enrichment application

[0142] 100 μL of plasma was vortexed for 1 min and then allowed to stand in the dark for 5 min. 150 μL of methanol was added and vortexed for 1 min. 200 μL of water was added and vortexed for 1 min. The mixture was centrifuged (4°C, 12000 rpm, 15 min). 300 μL of the supernatant was taken and 0.6 mg of the prepared material was added thereto. The mixture was vortexed for 30 min. The supernatant was removed and the material was washed with deionized water. 300 μL of methanol was added and vortexed for 25 min to elute the hormone. After magnetic separation, 200 μL of the supernatant was taken and blown to dryness with nitrogen. The mixture was then redissolved with 100 μL of 30% methanol and injected for measurement. The amounts of 25 steroid hormones including progesterone, 11-deoxycorticosterone, corticosterone, 18-hydroxycorticosterone, aldosterone, 17-hydroxypregnenolone, 17-hydroxyprogesterone, 11-deoxycortisol, 21-deoxycortisol, cortisol, cortisone, dehydroepiandrosterone, androstenedione, estrone, testosterone, estradiol, estriol, dihydroxytestosterone, 11-hydroxyandrostenedione, 11-ketoandrostenedione, 11-hydroxytestosterone, 11-ketotestosterone, epitestosterone, androstenone, and epiandrosterone were 0.04 ng / mL, 13.941 pg / mL, 2.239 ng / mL, 644.622 pg / mL, 94.707 pg / mL, 1.031 ng / mL, 0. 281ng / mL, 190.131pg / mL, 4.515pg / mL, 84.796ng / mL, 17.951ng / mL, 6.742ng / mL, 1835.636pg / mL, 1408.085pg / mL, 244.25pg / mL, 39.03 pg / mL, 486.838pg / mL, 207.834pg / mL, 656.5pg / mL, 35.181pg / mL, 1.142pg / mL, 100.04pg / mL, 14.482pg / mL, 518.899pg / mL, 5.346pg / mL.

[0143] Embodiment 20

[0144] A core-shell magnetic molecular imprinted polymer for practical blood sample enrichment application

[0145] 100 μL of plasma was vortexed for 1 min and then allowed to stand in the dark for 5 min. 150 μL of methanol was added and vortexed for 1 min. 200 μL of water was added and vortexed for 1 min. The mixture was centrifuged (4°C, 12000 rpm, 15 min). 300 μL of the supernatant was taken and 0.1 mg of the prepared material was added thereto. The mixture was vortexed for 30 min. The supernatant was removed and the material was washed with deionized water. 300 μL of methanol was added and vortexed for 25 min to elute the hormone. After magnetic separation, 200 μL of the supernatant was taken and blown to dryness with nitrogen. The mixture was then redissolved with 100 μL of 30% methanol and injected for measurement. The amounts of 25 steroid hormones including progesterone, 11-deoxycorticosterone, corticosterone, 18-hydroxycorticosterone, aldosterone, 17-hydroxypregnenolone, 17-hydroxyprogesterone, 11-deoxycortisol, 21-deoxycortisol, cortisol, cortisone, dehydroepiandrosterone, androstenedione, estrone, testosterone, estradiol, estriol, dihydroxytestosterone, 11-hydroxyandrostenedione, 11-ketoandrostenedione, 11-hydroxytestosterone, 11-ketotestosterone, epitestosterone, androstenone, and epiandrosterone were 0.058 ng / mL, 30.57 pg / mL, 1.318 ng / mL, 877.982 pg / mL, 106.729 pg / mL, 6.784 ng / mL, and 0. 872ng / mL, 442.913pg / mL, 2.984pg / mL, 74.26ng / mL, 29.466ng / mL, 5.246ng / mL, 443.882pg / mL, 476.369pg / mL, 103.155pg / mL, 2.097pg / mL, 2424.203pg / mL, 12.16pg / mL, 118.994pg / mL, 0.922pg / mL, 2.172pg / mL, 744.531pg / mL, 17.139pg / mL, 187.706pg / mL, 15.121pg / mL.

[0146] Embodiment 21

[0147] A core-shell magnetic molecular imprinted polymer for practical blood sample enrichment application

[0148] 100 μL of plasma was vortexed for 1 min and then allowed to stand in the dark for 5 min. 150 μL of methanol was added and vortexed for 1 min. 200 μL of water was added and vortexed for 1 min. The mixture was centrifuged (4°C, 12000 rpm, 15 min). 300 μL of the supernatant was taken and 0.3 mg of the prepared material was added thereto. The mixture was vortexed for 30 min. The supernatant was removed and the material was washed with deionized water. 300 μL of methanol was added and vortexed for 25 min to elute the hormone. After magnetic separation, 200 μL of the supernatant was taken and blown to dryness with nitrogen. The mixture was then redissolved with 100 μL of 30% methanol and injected for measurement. The amounts of 25 steroid hormones, progesterone, 11-deoxycorticosterone, corticosterone, 18-hydroxycorticosterone, aldosterone, 17-hydroxypregnenolone, 17-hydroxyprogesterone, 11-deoxycortisol, 21-deoxycortisol, cortisol, cortisone, dehydroepiandrosterone, androstenedione, estrone, testosterone, estradiol, estriol, dihydroxytestosterone, 11-hydroxyandrostenedione, 11-ketoandrostenedione, 11-hydroxytestosterone, 11-ketotestosterone, epitestosterone, androstenone, and epiandrosterone, were 0.051 ng / mL, 33.153 pg / mL, 2.843 ng / mL, 330.681 pg / mL, 57.131 pg / mL, 0.758 ng / mL, and 0.71 3ng / mL, 710.775pg / mL, 24.768pg / mL, 108.867ng / mL, 13.788ng / mL, 1.097ng / mL, 755.14pg / mL, 1644.834pg / mL, 49.125pg / mL, 21.726pg / mL, 2634.164pg / mL, 104.819pg / mL, 312.564pg / mL, 6.382pg / mL, 0.298pg / mL, 174.688pg / mL, 21.96pg / mL, 155.711pg / mL, 17.316pg / mL.

[0149] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and examples, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. The technical solutions and inventive concepts of the present invention can be equivalently replaced or changed, which are all within the scope of protection of the present invention. The present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a core-shell magnetic molecularly imprinted polymer material, characterized in that: Its preparation method is: 1) 0.41-1.22 g of anhydrous ferric chloride and 1.8-5.4 g of sodium acetate were dissolved in 50 mL of ethylene glycol, stirred evenly, and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and reacted in an oven at 200° C. for 8 h. After the reaction was completed, the precipitate was separated by magnetic attraction, and the obtained black ferrosoferric oxide nanoparticles were washed alternately with ethanol and deionized water three times, and placed in a 60° C. vacuum drying oven for 6 h; 2) 400-800 mg of the magnetic ferroferric oxide obtained above and 1 mol / L hydrochloric acid were mixed and ultrasonically treated for 10 min to activate the surface hydroxyl groups of the ferroferric oxide nanoparticles, and then the mixture was washed three times with deionized water to remove excess hydrochloric acid, and then dispersed in 200 mL of ethanol / water with a volume ratio of 4:

1. The mixture was ultrasonically treated for 20 min to fully disperse the mixture, and 5 mL of ammonia water was added thereto under mechanical stirring, and then 400-1200 μL of TEOS was diluted to 20 mL with ethanol, and then the mixture was dripped into the reaction system at a speed of 1 d / s under the condition of mechanical stirring at 500 r / min, and the reaction was continued at room temperature with mechanical stirring for 5 h. After the reaction was completed, the precipitate was separated by magnetic attraction, and the obtained black product was washed alternately with ethanol and deionized water three times, and then placed in a vacuum drying oven at 60°C for 6 h to obtain silica-modified ferroferric oxide nanoparticles; 3) Add silica-modified magnetic ferroferric oxide nanoparticles, 3,3-dihydroxybenzidine and betamethasone to 40 mL of ethanol solution respectively, and disperse them uniformly by ultrasonication at room temperature; then dissolve p-benzoquinone in 60 mL of ethanol solution, and drip it into the above reaction system at a speed of 1 d / s under mechanical stirring at 500 r / min, and condense and reflux at 70°C for 2 h. After the reaction, elute the template molecule with a solution of methanol / acetic acid with a volume ratio of 9:1, and then wash it alternately with deionized water and ethanol, and then put it into a 60°C oven for drying for 6 h; wherein, the magnetic ferroferric oxide nanoparticles are 100 mg, the betamethasone is 40 mg, the molar ratio of betamethasone to 3,3-dihydroxybenzidine is 1:2-1:10, and the molar ratio of betamethasone to p-benzoquinone is 1:10-1:

50.

2. A core-shell magnetic molecular imprinted polymer material, characterized in that: It is prepared according to the preparation method of a core-shell magnetic molecular imprinted polymer material according to claim 1; the core of the core-shell magnetic molecular imprinted polymer material is a silicon dioxide-modified ferroferric oxide nanoparticle, and the shell is an imprinted polymer layer of 3,3-dihydroxybenzidine and p-benzoquinone with betamethasone as a virtual template, which is a rough particle of 400 to 900 nm.

3. An application of a core-shell magnetic molecular imprinted polymer material, characterized in that: It is an application of a core-shell magnetic molecular imprinting polymer material according to claim 2, which is used for enriching 25 steroid hormones in blood samples: 100 μL of plasma is vortexed for 1 minute and then kept still in the dark for 5 minutes, 150 μL of methanol is added, vortexed for 1 minute, 200 μL of water is added, vortexed for 1 minute, centrifuged at 4°C, 12000rpm, 15 minutes, 300 μL of supernatant is taken, 0.1-0.6 mg of the prepared material is added thereto, vortexed for 30 minutes, the supernatant is removed, the material is washed with deionized water, 300 μL of methanol is added, vortexed for 25 minutes to elute the hormones, after magnetic separation, 200 μL of supernatant is taken, blown to dryness with nitrogen, and then redissolved with 100 μL of 30% methanol and sampled for measurement.

Citation Information

Patent Citations

  • Magnetic nano-crystal cellulose grafted graphene oxide surface molecularly imprinted polymer

    CN107129562A

  • Magnetic super-crosslinked organic polymer material and preparation method and application thereof

    CN111530431A

Cited By

  • A Highly Efficient Extraction and Preservation Method for Serum BICC1 Natural Protein

    CN120714599B